Analysis on Facilitative Supervision of Primary Healthcare Center Coordinator Midwives to BPM ConcerningPregnancy and Delivery Services in Semarang City - Dewi Laila Mahligai Putri; Sri Achadi Nugraheni; Atik Mawarni (Jurnal Manajemen Kesehatan Indonesia, 2013)
Supervisi fasilitatif bidan koordinator (bikor) puskesmas terhadap bidan praktek mandiri (BPM)merupakan pembinaan klinis dan manajemen yang dilakukan secara berkesinambungan sertatepat sasaran. Pelaksanaan supervisi fasilitatif yang dilakukan selama ini belum optimal,sehingga perlu upaya pengkajian lebih lanjut. Penelitian ini bertujuan untuk menganalisispelaksanaan supervisi fasilitatif bidan koordinator puskesmas terhadap BPM terkait pelayanankehamilan dan persalinan di Kota Semarang. Penelitian ini menggunakan pendekatan kualitatif.Analisis data menggunakan metode analisis isi (content analysis). Variabel dalam penelitian inimeliputi aspek yang dibina (aspek klinis, non klinis, logistik dan manajemen), cara penilaian dan langkah pelaksanaan. Hasil penelitian menunjukkan bahwa supervisi meliputi semua aspek yang dibina. Belum semua bikor menggunakan daftar tilik asuhan persalinan. Supervisi aspek klinis tidak dilakukan dengan pengamatan langsung. Langkah pelaksanaan pra supervisi : belum ada pelatihan supervisi fasilitatif bagi bikor puskesmas dan buku acuan supervisi fasilitatif tidak diberikan. Langkah pelaksanaan supervisi belum sesuai acuan, karena sifatnya inspeksi mendadak. Disarankan kepada Dinas Kesehatan untuk mengadakan pelatihan supervisi fasilitatif bagi semua bidan koordinator puskesmas. Bagi puskesmas membuat kesepakatan dengan BPM terkait jadual supervisi fasilitatif.Facilitative supervision of primary healthcare center (puskesmas) coordinator midwife (bikor) to self-employed practice midwives (BPM) constituted an ongoing and on-target clinical andmanagerial supervision. Current implementation of facilitative supervision was not optimum;therefore, further study was required. Objective of this study was to analyze the implementation of facilitative supervision of primary healthcare coordinator midwives to BPM concerning pregnancy and delivery services in Semarang city. A qualitative approach was applied in this study. Data were analyzed using content analysis method. Study variables were supervised aspects (clinical, non-clinical, logistic, and managerial aspects), assessment method and implementation stages. Results of the study showed that supervision had included all supervised aspects. Not all bikor used delivery care list. Supervision on clinical aspect did not include direct observation. Pre supervision implementation steps: facilitative supervision training for bikor of the primary healthcare centers had not been done, reference book for facilitative supervision had not been distributed. Steps of the implementation of supervision were not performed according to the guidelines. This was caused by on the spot implementation of supervision.Suggestion for District Health Office is to conduct facilitative supervision for all primary healthcare centers coordinator midwives. Suggestion for primary healthcare center is to make agreement with BPM concerning facilitative supervision schedule